Economic Analysis of Vulnerability and Capacity: A Study of Water Logging, Bhobodah, Keshabpur, Jessore - Mizanuzzaman, Md. (American International Journal of Social Science Research, 2017)
Global environmental change and sustainability science increasingly recognize the need to address the consequences of changes taking place in the structure and function of the biosphere. These changes raise questions such as: Who and what are vulnerable to the multiple environmental changes underway, and where? This recognition requires revisions and enlargements in the basic design of vulnerability assessments, including the capacity to treat coupled human–environment systems and those linkages within and without the systems that affect their vulnerability. A vulnerability framework for the assessment of coupled human–environment systems is presented. (Turner. et.al).This study is related with economic analysis of vulnerability and capacity contextually Jessore’s village.